Dissociations constants and association thermodynamic function of glycine acid in dimethy formaide mixtures from conductance measurements - Ahlam M. Farhan; Qhatan Adnan Yousife (مجلة بغداد للعلوم)
the dissociation of glycine in dimethyl formamide mixture over the temperature range 293.15-308.15 K.